A Desccriptive Study on the Use of Code Mixing by the English Teacher at SMAN Bali Mandara in the Academic Year 2014/2015 - N M.G. Purnamasari; I Nyoman Adi Jaya Putra; Ni Komang Arie Suwastini (Lingua Scientia, 2016)
This study aimed at finding out the process of code mixing, the reasons of using code mixing by English teacher of grade X and knowing the students’ responses on the use of code mixing used by their English teacher at SMAN Bali Mandara in the academic year 2014/2015. This research was conducted by using descriptive qualitative design. The instruments used in this study were observation sheet, audio recorder, interview guide and questionnaires. Accordingly, the data accumulation showed that there was 84 sentences, classified as insertion processes, and then 37 sentences belonged to alternation process, and the last there were 14 sentences, classified as congruent lexicalization processes. The reasons of using code mixing were, 1) to make intention of clarifying the speech content for interlocutor, 2) to be emphatic about something, 3) there is no appropriate word which can be understood by the students, 4) to help the teacher to create relax situation, and 5) to quote somebody else.